Improving crude protein and methionine production, selective lignin degradation and digestibility of wheat straw by Inonotus obliquus using response surface methodology. (14th August 2021) - Zang, Qiang; Chen, Xiaoxiao; Zhang, Chao; Lin, Mengmeng; Xu, Xiangqun
Abstract: BACKGROUND: To date, fungus‐assisted pretreatment of agricultural residue has not become the preferred method to produce protein‐enriched and ruminally digestible animal feed because of low time efficiency of fungal delignification and protein production, i.e. the long solid‐state fermentation period, and because of laccase as a potential inhibitor of cellulose activity. In this study, response surface methodology was employed to optimize the parameters in the process of producing nutritious animal feed from wheat straw with Inonotus obliquus pretreatment. RESULTS: The mineral salt solution containing ( w/v ) (NH4 )2 SO4 1%, MgSO4 ·7H2 O 0.03%, KH2 PO4 0.011%, Tween‐80 0.4%, and corn starch 10% with pH of 7.4 was optimized. Inonotus obliquus rapidly and completely colonized on wheat straw with an ergosterol content of 280 μg g −1 dry matter, consuming 45% of lignin after 15 days of fermentation, producing maximums of lignin peroxidase (1729 IU g −1 ), manganese peroxidase (610 IU g −1 ) and laccase (98 IU g −1 ) on days 5, 15, and 25, respectively. The crude protein (102.4 g kg −1 ) of 15‐day fermented wheat straw increased by ~132%. After hydrolysis, the essential protein‐bound amino acids (15.3 g kg −1 ) increased by ~47%, within which Met and Lys measured ~1070% and ~60% higher. The treatment with I. obliquus also improved the in vitro gas production after 72 h (IVGP72 ) of wheat straw to 178.8 mL g −1 organic matter (~43% increase). CONCLUSION: For the first time, we found that I. obliquus is an effective white rot fungus turning wheat straw into ruminally digestible animal feed without laccase inhibitor.